2023
DOI: 10.3389/fcvm.2023.1155861
|View full text |Cite
|
Sign up to set email alerts
|

ehealth technology in cardiac exercise therapeutics for pediatric patients with congenital and acquired heart conditions: a summary of evidence and future directions

David A. White,
Aimee M. Layton,
Tracy Curran
et al.

Abstract: Many children and adolescents with congenital and acquired heart disease (CHD) are physically inactive and participate in an insufficient amount of moderate-to-vigorous intensity exercise. Although physical activity (PA) and exercise interventions are effective at improving short- and long-term physiological and psychosocial outcomes in youth with CHD, several barriers including resource limitations, financial costs, and knowledge inhibit widespread implementation and dissemination of these beneficial programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 128 publications
0
1
0
Order By: Relevance
“…[ 73 ] indicates that nearly 80% of patients with CHD experience symptoms of anxiety and depression. Recent research [ 20 , 74 ] has suggested that the use of mHealth apps can improve symptoms related to anxiety and depression. Our study found that the mHealth groups experienced a decrease in SAS and SDS scores compared to the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…[ 73 ] indicates that nearly 80% of patients with CHD experience symptoms of anxiety and depression. Recent research [ 20 , 74 ] has suggested that the use of mHealth apps can improve symptoms related to anxiety and depression. Our study found that the mHealth groups experienced a decrease in SAS and SDS scores compared to the control groups.…”
Section: Discussionmentioning
confidence: 99%